رؤية مقترحة لتحويل الكليات التقنية في المملكة العربية السعودية - الفرهود, صالح (جامعة الوادي - University of Eloued, 2019)
سعت الدراسة إلى اقتراح رؤية لتحويل الكليات التقنية إلى منظمات متعلمة. وتكون مجتمع الدراسة من جميع أعضاء الهيئة التدريبية في الكليات التقنية للبنين للعام (2016) وعددهم (3817) عضوًا. وتم اختيار عينة عشوائية طبقية من (383) عضو هيئة تدريب. وتمّ تطوير أداة من (67) فقرة، لقياس درجة ممارسة أبعاد المنظمة المتعلمة في ضوء نموذج "مارسك ووتكنز"، وتشمل سبعة أبعاد، هي: تشجيع الحوار، وتعلم الفريق، وإنشاء فرص التعلم المستمر، والقيادة الاستراتيجية، وأنظمة مشاركة المعرفة، وربط المنظمة مع البيئة الخارجية. وتم التحقق من دلالات صدقها وثباتها. وأظهرت النتائج أن درجة ممارسة أبعاد المنظمة المتعلمة في الكليات التقنية كانت منخفضة. كما أظهرت وجود فروق دالة إحصائيا في استجابات العينة تعزى إلى متغير المسمى الوظيفي ومتغير طبيعة العمل الحالي.وقام الباحث بتطوير رؤية من (68) ممارسة تربوية في ضوء نموذج "مارسك ووتكنز" لتحويل الكليات التقنية إلى منظمات متعلمة. ABSTRACT:The study aims to propose Vision To Conversion Technical Colleges To A learning Organization. sample was randomly stratum selected, consisted of(n=383). An instrument was developed to measure the practice degree of dimensions of learning organization in light of "Marsik & Watkins" Model. The questionnaire consisted of(67) items, and include seven dimensions: promote dialogue, team learning, continuous learning opportunitie, empower people towards a collective vision, the strategic leadership, create systems to share learning and connect with environment. were verified validity and reliability of a questionnaire. The results showed that the degree of practice of dimensions the learning organization at was low. There are statistically significant differences among the means of the responses of the sample's individuals according to variable of job title and current work. was developed Vision to Conversion Technical Colleges in to A learning Organization. The overall framework of the proposed vision consisted of(68) educational practice.
إلى منظمات متعلمة
مقال
Keywords: المنظمة المتعلمة ; الكليات التقنية; learning Organization; Technical Colleges; "Marsik & Watkins" Model.